ABOUT THE WORK OF MUHAMMAD IBN MUSA AL-KHOREZMI “AL-KITAB AL-MUHTASAR HISAB AL-JABR WAL-MUKOBALA " (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In article is brought great encyclopedist scientist end VII ages and begin VIII ages crisp about mathematician Al- Horazmiy. This article about his (its) work on mathematician and about book.